A new species of Agaricus sect. Brunneopicti from Eastern India - Tarafder, Entaj; Dutta, Arun Kumar; Sarkar, Jit; Acharya, Krishnendu (Phytotaxa, 2018)
Agaricus duplocingulatoides (Agaricaceae, Agaricales, Basidiomycota) is proposed here as new to science based on collections made from West Bengal, Eastern India. The morphological features together with molecular data confirms its placement in Agaricus sect. Brunneopicti within Agaricus subg. Pseudochitonia. A comprehensive description, illustrations and comparison with morphologically and phylogenetically related taxa are provided.